Problema Perempuan Dalam Memilih Produk Unggulan Bank Syariah Mandiri (BSM) - Rahim, Abdul (PSW, 2012)
Abstract: Islamic banking has developed from year to year although it is not growing as rapidly as conventional banking, due to various factors, including many conventional banks have greater assets. However, Islamic banking is also experiencing growth as well as experiencing difficulties in its development among other aspects of the law, lack of socialization of Islamic banking, syariâah banking operational constrains as well as the publicâs understanding of syariah banking is still relatively unfamiliar.Constrains, will provide the solution to be studied and analyzed in accordance with the facts that exist in the community, and it is an input as well as valuable lessons for future Islamic banking tobe developed in the future.